1998
DOI: 10.1136/gut.42.2.251
|View full text |Cite
|
Sign up to set email alerts
|

Motor function of the proximal stomach and visceral perception in gastro-oesophageal reflux disease

Abstract: Background-The abnormally high postprandial rate of transient lower oesophageal sphincter relaxations seen in patients with reflux disease may be related to altered proximal gastric motor function. Heightened visceral sensitivity may also contribute to reporting of symptoms in these patients. Aims-To assess motor function of the proximal stomach and visceral perception in reflux disease with a barostat. Methods-Fastingand postprandial proximal gastric motility, sensation, and symptoms were measured in nine pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
77
3
12

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(98 citation statements)
references
References 40 publications
6
77
3
12
Order By: Relevance
“…In terms of mechanisms underlying these relationships in elderly GERD patients, both the intra-abdominal pressure increased by spinal kyphotic deformity and esophageal hiatus hernia can be caused (10,12). The literature contains several reports of poor gastric emptying in GERD patients (6,19,20,25). In recent years electrogastrography (EGG), a method that records the myoelectrical signal from the gastric smooth muscle through electrodes positioned on the abdominal skin (2), has been utilized to evaluate gastric function in a non-invasive manner (4).…”
mentioning
confidence: 99%
“…In terms of mechanisms underlying these relationships in elderly GERD patients, both the intra-abdominal pressure increased by spinal kyphotic deformity and esophageal hiatus hernia can be caused (10,12). The literature contains several reports of poor gastric emptying in GERD patients (6,19,20,25). In recent years electrogastrography (EGG), a method that records the myoelectrical signal from the gastric smooth muscle through electrodes positioned on the abdominal skin (2), has been utilized to evaluate gastric function in a non-invasive manner (4).…”
mentioning
confidence: 99%
“…Some data suggest that the physiological postprandial increase in transient LES relaxations is more marked and prolonged in patients with GER disease than in controls (11). Although this could be partly due to a delayed recovery of proximal gastric tone after a meal (20), it is possible to hypothesize impaired adaptation of the rate of transient LES relaxation to prolonged gastric distension, which may be secondary to the autonomic nerve dysfunction already described in patients with GER disease (4,5).…”
Section: Discussionmentioning
confidence: 89%
“…Based on studies showing that patients with GERD may have regional gastric motor abnormalities (16)(17)(18)(19)(20) and that the IJ area of C.L.A. Barbieri et al…”
Section: Discussionmentioning
confidence: 99%
“…Also, delayed gastric emptying, which might cause distension of the stomach, has been reported in substantial proportions of patients with GERD (8)(9)(10)(11)(12), although others have failed to confirm this finding (13)(14)(15)(16). More recently, it has been shown that patients with GERD may have regional disturbances of gastric motility, such as increased (16)(17)(18)(19) or decreased (20) retention of chyme in the proximal stomach, which may occur independently of gastric emptying rates.…”
Section: Introductionmentioning
confidence: 99%